2010
DOI: 10.3354/meps08546
|View full text |Cite
|
Sign up to set email alerts
|

Environmental influences on the occurrence of coastal sharks in estuarine waters

Abstract: Long-term fisheries independent gill net surveys conducted in Texas estuaries from 1975 to 2006 were used to develop spatially explicit estuarine habitat use models for 3 coastal shark species: bull shark Carcharhinus leucas, blacktip shark C. limbatus, and bonnethead shark Sphyrna tiburo. Relationships between environmental predictors and shark distribution were investigated using boosted regression trees (BRT). Bull shark was the most abundant species (n = 5800), followed by blacktip (n = 2094), and bonnethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
141
3
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(159 citation statements)
references
References 47 publications
13
141
3
2
Order By: Relevance
“…Similarly, Castro (1993) and Ulrich et al (2007) documented the presence of sharks in South Carolina estuaries after water temperatures reached ∼19-20 • C. Increasing shark abundance at higher temperatures is also expected. In the coastal waters of Texas, Froeschke et al (2010) showed that shark catch rates increased as temperatures increased between 20 • C and 30 • C, a trend also seen in the present study. Also, coastal waters tend to be warmest during summer months when parturition for species like Atlantic Sharpnose and Blacktip sharks occurs (Castro 2011:509-513), resulting in increased shark catches, particularly of age-0 individuals (Parsons and Hoffmayer 2007).…”
Section: Discussionsupporting
confidence: 75%
“…Similarly, Castro (1993) and Ulrich et al (2007) documented the presence of sharks in South Carolina estuaries after water temperatures reached ∼19-20 • C. Increasing shark abundance at higher temperatures is also expected. In the coastal waters of Texas, Froeschke et al (2010) showed that shark catch rates increased as temperatures increased between 20 • C and 30 • C, a trend also seen in the present study. Also, coastal waters tend to be warmest during summer months when parturition for species like Atlantic Sharpnose and Blacktip sharks occurs (Castro 2011:509-513), resulting in increased shark catches, particularly of age-0 individuals (Parsons and Hoffmayer 2007).…”
Section: Discussionsupporting
confidence: 75%
“…Many estuarine species (including Southern Flounder) spawn offshore and juveniles recruit into estuaries via tidal inlets (Nañez-James et al 2009). As a result, the abundance of such species is often greatest near inlets during the fall spawning season (Whaley et al 2007;Froeschke et al 2010Froeschke et al , 2013b. Our results also indicate greater abundance in the areas furthest from the inlets.…”
Section: Discussionsupporting
confidence: 68%
“…Soak time was used as an additional explanatory variable to control for effort-related effects on catch (Maunder and Punt 2004). The distance from each sample location to the nearest tidal inlet was calculated using the cost-distance function in ArcGIS (Whaley et al 2007;Froeschke et al 2010). Two cost-distance surfaces were created, one without Packery Channel inlet (which did not open until June 2005; Figure 1) and one that included Packery Channel inlet (which applied to all sampling events after June 2005).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Species that exhibit such site fidelity provide an opportunity to examine how environmental changes affect movement patterns [14]. While factors that influence Bonnethead movements have been well studied in the eastern GOM [6,16], comparatively less is known about the movements of this species in the northern GOM [but see 17]. Identifying the region-specific factors influencing the distribution of this species is essential for understanding potential impacts induced from anthropogenic alterations to coastal ecosystems.…”
mentioning
confidence: 99%